Clinical characterization of CCT2 and its role in autophagy regulation during age-related macular degeneration - Lin Wang; Ling-xiao Wang; Mu-ye Li; Rong Zhang; Guo-hong Zhou (Scientific Reports)
Abstract Age-related macular degeneration (AMD) is the leading cause of vision loss in the elderly, and the role of chaperonin containing TCP1 subunit 2 (CCT2) remains unclear. This study aims to elucidate the mechanistic link between CCT2 and AMD, contributing to improved understanding and potential therapeutic strategies. Retinal and RPE-Choroid transcriptome array data from 130 AMD patients and 121 normal donors (GSE29801 dataset) were reanalyzed to assess CCT2 expression across different AMD subtypes, age groups, and genders. Single-sample gene set enrichment analysis was performed to explore correlations with autophagy-related genes and other established AMD causes. Additionally, CCT2 expression was validated in sodium iodate (NaIO₃)-induced 661 W cells (photoreceptor-like cells) using quantitative real-time PCR (qRT-PCR). CCT2 was significantly enriched in advanced AMD retinas compared to intermediate stages in retina (both macular and extramacular) and early stages in extramacular retina (p < 0.05). NaIO3-treated 661 W cells exhibited a similar expression trend, confirming transcriptomic findings. CCT2 is significantly upregulated in advanced AMD and may contribute to drusen degradation. It shows potential as both a biomarker and an independent diagnostic indicator, particularly for advanced-stage AMD.